Imagination and Rigor Essays on Eduardo R. Caianiello$1 (Bs Scientific Heritage /s - Termini, Settimo; SpringerLink (Online service) (Milano : Springer Milan, 2006)
The aim of this Volume of scientific essays is twofold. From one side, by remembering the scientific figure of Eduardo R. Caianiello, it aims at focusing his outstanding contributions - from theoretical physics to cybernetics - which after so many years still represent occasion of innovative paths to be fruitfully followed. It must be stressed the contribution that his interdisciplinary methodology can still be of great help in affording and solving present day complex problems. On the other side, it aims at pinpointing with the help of the scientists contributing to the Volume - some crucial problems in present day research in the fields of interest of Eduardo Caianiello and which are still among the main lines of investigation of some of the Istitutes founded by Eduardo (Istituto di Cibernetica del CNR, IIAS, etc).
Pattern Discovery in the Crib of Procrustes -- Close Encounters With Far Ideas -- Remarks on the Semantics of (3z(BInformation(3y (B-- Simulation Models of Organism Behavior: Some Lessons from Precybernetic and Cybernetic Approaches -- Caianiello and Neural Nets -- Computability, Computation, and the Real World -- Structure, Combinatorics, and Complexity of (3z(BWords(3y (B-- Quantum Field Theory and Renormalization Theory in the Early Scientific Activity of Eduardo R. Caianiello -- The Renormalization Group from Bogoliubov to Wilson -- Caianiello$1 (Bs Maximal Acceleration. Recent Developments -- Modeling Single Neuron Activity in the Presence of Refractoriness: New Contributions to an Old Problem -- Cosmological Implications of Caianiello$1 (Bs Quantum Geometry -- Imagination and Rigor: Their Interaction Along the Way to Measuring Fuzziness and Doing Other Strange Things -- Rational vs Reasonable -- Eduardo.s
Keywords: Physics; Computer science; Astronomy; Astrophysics; Cosmology; Statistical physics; Dynamical systems; Physics; Physics, general; Computer Science, general; Statistical Physics, Dynamical Systems and Complexity; Astronomy, Astrophysics and Cosmology; Electronic books